Pengaruh Perlakuan Alkali Pada Serat Agave dan Ketebalan Inti Terhadap Kekuatan Bending Komposit Sandwich Serat Agave-Polyester dengan Inti Kayu Olahan (Engineering Wood) - Ferriawan Yudhanto (Teknoin, 2015)
Fibers and synthetic core as a component of composite sandwich proved costly and environmentally unfriendly, while Indonesia's natural resources will be very abundant natural materials and also supported human resources still need a lot of land to work. So back to nature is a smart move and wise for the condition. Innovation of the natural material made to eliminate weaknesses in their mechanical properties. Particle Wood or particle board  can be used as a component of composite sandwich. In this research, the manufacture of composite sandwich with skin  of agave or sisal fibers (random distribution) and core of composit  sandwich is  particle board. Variable thickness of the core wood used is 10 and 15 mm. In the process of making the sandwich composite wood core is made through compression molding process by means of pressing the composite mold. The presence alkali treatment of agave or sisal  fibre at 2 % Concentration NaOH solvent. The results showed a composite sandwich with a span length of 60 mm has an average bending moments in composite sandwich with 10 mm thick core of 24,4 N/mm2 and for 15 mm thick core of 16,3  N/mm2. Sampling Bending Strength Test 3 pieces each test sample. Macro Fracture from bending test  is dominated the damage intererface failure between core and skins,  fiber pull out,  failed to pull and shear fracture core. The alkali treatment 2% solvent of NaOH for 2 (two) hours increase 12 % bending stress.